A Novel Unit Power Factor Rectifier Based on Three-phase Digital PLL - Xuegui Zhu; Zhihong Fu; Xiangfeng Su (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
A novel three-phase phase-locked loop solution is proposed based on D-Q transformation aiming at the AC-DC rectifier with high efficiency and high power factor. The phase-locked loop is implemented digitally using the Xilinx blockset integrated with Matlab/Simulink. The three-phase digital phase-locked loop (TDPLL) is elaborately designed with the parameters defined in detail. The AC-DC converter (rectifier) model with the TDPLL is built and simulated in the high-speed VHS-ADC simulation platform from Canada. The simulation and test results show the TDPLL is locked right after the different three-phase voltage disturbances and very suitable for control of the rectifier with high parallelism through space vector pulse width modulation (SVPWM). http://dx.doi.org/10.11591/telkomnika.v11i7.2850